STUDENT MOTIVATION IN PARTICIPATING IN PHYSICAL EDUCATION, SPORTS, AND HEALTH CLASSES - Akip Sugiharto; Mohammad Syaifuddin; Ria A. Asih (JURNAL EDUSCIENCE, 2026)
Purpose – This research aims to determine: 1) student motivation in following Physical Education, Sports, and Health (PESH) learning in elementary schools, 2) students' external motivation in following PESH learning in elementary schools, 3) students' internal motivation in following PESH learning in elementary schools, and 4) the inhibiting and supporting factors for students in following PESH learning in elementary schoolsMethodology – This research uses a quantitative descriptive approach, with a survey and data collection via a checklist questionnaire instrument. The population in this study was 29 students in class 5A at SD Muhammadiyah 2, Bojonegoro, during the 2024/2025 academic year who met the inclusive criteria. The data collected through the questionnaire were analyzed using quantitative descriptive techniques, with percentages.Findings – The scope of this study focuses on the motivation of elementary school students in participating in Physical Education, Sports, and Health (PESH) lessons. The motivation studied comprises two main aspects: internal and external motivation.Internal motivation includes drives originating within the student, such as interest, enjoyment, and the desire to excel in PSEH learning. Meanwhile, external motivation includes influences from outside the student, such as teaching methods, the use of learning tools and media, and the learning environment.Contribution –the results of this study serve as input to understand better the learning process of Physical Education, Sports, and Health, so that learning activities can be optimized.